2(x-4)+12=x-4(6+2x)+9

Simple and best practice solution for 2(x-4)+12=x-4(6+2x)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)+12=x-4(6+2x)+9 equation:


Simplifying
2(x + -4) + 12 = x + -4(6 + 2x) + 9

Reorder the terms:
2(-4 + x) + 12 = x + -4(6 + 2x) + 9
(-4 * 2 + x * 2) + 12 = x + -4(6 + 2x) + 9
(-8 + 2x) + 12 = x + -4(6 + 2x) + 9

Reorder the terms:
-8 + 12 + 2x = x + -4(6 + 2x) + 9

Combine like terms: -8 + 12 = 4
4 + 2x = x + -4(6 + 2x) + 9
4 + 2x = x + (6 * -4 + 2x * -4) + 9
4 + 2x = x + (-24 + -8x) + 9

Reorder the terms:
4 + 2x = -24 + 9 + x + -8x

Combine like terms: -24 + 9 = -15
4 + 2x = -15 + x + -8x

Combine like terms: x + -8x = -7x
4 + 2x = -15 + -7x

Solving
4 + 2x = -15 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
4 + 2x + 7x = -15 + -7x + 7x

Combine like terms: 2x + 7x = 9x
4 + 9x = -15 + -7x + 7x

Combine like terms: -7x + 7x = 0
4 + 9x = -15 + 0
4 + 9x = -15

Add '-4' to each side of the equation.
4 + -4 + 9x = -15 + -4

Combine like terms: 4 + -4 = 0
0 + 9x = -15 + -4
9x = -15 + -4

Combine like terms: -15 + -4 = -19
9x = -19

Divide each side by '9'.
x = -2.111111111

Simplifying
x = -2.111111111

See similar equations:

| 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r | | -6x+3=-6x-5 | | 4x+7x-8=-19 | | 40=5e | | 3x^2+7=301 | | 5+2x=3x+-4 | | -x-29=37-4x | | x^2+x-280=0 | | 72x^2+144x-1080=0 | | 3.08/1.4 | | F(x)=SEN(5x+2y) | | 2/x^2-4 | | 5=-2k+21 | | 3x+20=5x+20 | | 0=3b^2+6b | | 2ln(X-5)+4=12 | | 4/2x-20 | | 8x-18=2x+18 | | 4(2x-11)-6x=8 | | 3x^3=12x^2 | | 13x-11=10x+1 | | (6/7wz^5)(1/5w^3z^3) | | 5/1m=22 | | -x-4x=25 | | x^2+2=44 | | -12x=3.6 | | 38(10-3.5x)=13(3x-8)+36.8 | | Y=-16t^2+90t+70 |

Equations solver categories